937. PASSIFLORA PUNICEA. (16th May 2020) - Vanderplank, John; King, Christabel
Summary: Passiflora punicea Ruiz & Pavón ex DC., considered by Maxwell T. Masters (1872) and E. P. Killip (1938) to be a synonym of P. vitifolia Kunth is here reinstated at species rank. It is described and illustrated in colour and with black and white line drawings. Its history, distribution, similarities to related species and cultivation are discussed. A key to its closest related species is provided.